تاثير فاعلية التمرينات بتركيز الانتباه في تعلم مهارة التمرير من الاسفل بالكرة الطائرة لطلاب المرحلة الثانية في كلية التربية البدنية وعلوم لرياضة - Ahmed Abdel Sattar Abdel Qader (Mustansiriyah Journal of Sports Science, 2024)
The research aims to use the effectiveness of attention-focusing exercises in the process of teaching students to pass from the bottom with volleyball, which has an important and fundamental role in improving the skill aspect and enabling students to achieve the goal with excellence and with the least possible amount of errors. The researcher used the experimental method to adapt it to the nature of the problem in the manner of two groups with the same Pre- and post-test. The research community consists of second-year students at the College of Physical Education and Sports Sciences/University of Baghdad for the academic year 2021-2022, who number (185) students distributed among seven academic divisions. The research sample was chosen intentionally by drawing lots, as it consisted of two groups (B) and (E) of males who were divided into experimental and control groups, as group (B) reached (29) students, while group (E) reached (29) students. 28) With (16) students for each group, thus the total number of the research sample is (32) students out of (185) students and constitutes a percentage of (17.297%) of the research community, which is an appropriate percentage to faithfully represent the community. The results of the research were significant and in favor of the experimental group due to the effectiveness of the exercises that were used to focus attention and learn the skill of passing from below. Keywords: (effectiveness of exercises, focusing attention, passing from below, volleyball).